Development of Local Wisdom-Based Animated Videos to Improve Procedure Text Writing Skills - Sugiyarti, Rita; Sukasih, Sri (Universitas Negeri Malang, 2024)
This research aims to create animated video content based on local wisdom to enhance students' proficiency in creating procedure texts. This study, which falls under research and development (R&D), employed the ADDIE paradigm, which has five stages: analysis, design, development, implementation, and evaluation. The evaluation of media development included 23 fourth-graders, two teachers, and material and media validation. The methods used to acquire the data included performance, documentation, interviews, observation, and questionnaires. The paired t-test and the N-gain test were used for the final data analysis, while the normality test was employed for the initial data analysis. The results of media validation by material experts obtained a percentage of 91% (very feasible), and media experts obtained a percentage of 90% (very feasible). The results of the pretest and post-test assessments were calculated using N-gain for small groups to increase by 74% with an average difference of 30% and for large groups to increase by 68% with an average difference of 24%. The t-test was used to assess the difference. The results of the pretest and post-test evaluations showed a significant difference, with a value of 0.000009<0.05 for the small group and a value of 0.000000002<0.05 for the large group. Based on these data, it can be concluded that making local wisdom-based animated video media to improve students' procedure text writing skills is valid, feasible and effective to be used in the learning process.